Modern weapons and military equipment for issue 1-2018 - Vučković, Dragan M. (Vojnotehnički glasnik / Military Technical Courier, 2017)
Ukraine's Tough T-84 Oplot-M Tank Won't Fight Russia (And Is Being Sold to Thailand?). Russia develops air-bursting ammunition. Assessing the capabilities of China’s Type 055 Destroyer. France Just Showed off a New Tank Sporting a Massive Main Gun. Serbian weaponry in foreign websites.